DEVELOPMENT OF INTERACTIVE LEARNING MEDIA BASED ON ARTICULATE STORYLINE IN THE CONTEXT OF BETAWI TRADITIONAL HOUSE TO IMPROVE MATHEMATICAL REASONING SKILLS - Purwati, Echa; Fortuna, Haura Putri; Faidina, Aisyah Rose; Kurniasih, Eka Rachma (FKIP Universitas Muhammadiyah Tangerang, 2025)
The integration of technology in education, particularly through the creation of interactive learning media, has gained significant attention as a means to enhance the quality of teaching and learning. Developing interactive learning media that incorporates the context of the Betawi Traditional House is essential, given that current educational resources, especially in mathematics, often lack real-world context. This study was conducted at a junior high school in Jakarta, focusing on seventh-grade students during the even semester of the 2023/2024 academic year. The research employed a Research and Development (R&D) approach, utilizing the Articulate Storyline platform to create interactive learning media, guided by the ADDIE development model. Data were collected through a questionnaire and essay questions, which included five items targeting mathematical reasoning skills. The questionnaire underwent validation by experts, and students provided feedback on the learning media via a separate questionnaire. Analysis of pre-test and post-test scores, using a one-sample t-test, indicated a notable improvement in post-test results compared to pre-test scores. Among the 33 participating students, the highest pre-test score was 12, achieved by just one student, while the post-test's highest score reached 18, accomplished by two students. The interactive learning media, presented as LKPD based on Articulate Storyline and contextualized within the Betawi Traditional House, is effectively designed to enhance students' mathematical reasoning skills in the study of Lines and Angles. This demonstrates that the developed learning media, validated and practical in nature, can significantly boost students' mathematical reasoning abilities.